2008
DOI: 10.1016/j.addbeh.2008.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Risk for excessive alcohol use and drinking-related problems in college student athletes

Abstract: There is compelling evidence that college student athletes engage in frequent episodes of heavy drinking and are prone to negative consequences resulting from such use. This study sought to identify risk and protective factors associated with student-athlete drinking and determine if studentathlete risk factors differed from those of non-athletes. Athletes compared to non-athletes reported more exaggerated perceptions of peer heavy drinking and lower sensation seeking and coping and enhancement motives for dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 59 publications
3
57
0
Order By: Relevance
“…The potential psychological effect of this stress is further highlighted by the findings on alcohol use among athletes [17]. College athletes are often reported to engage in higher and more risky alcohol use than their non-athlete peers [18][19][20], and it was found that one of the most frequently described reasons for alcohol use among athletes was to alleviate the stress of college life [17]. Due to the previous findings suggesting freshmen athletes experience unique stressors [13], this study will assess the impact of academic class on depression symptom severity.…”
Section: Daily Stressmentioning
confidence: 89%
“…The potential psychological effect of this stress is further highlighted by the findings on alcohol use among athletes [17]. College athletes are often reported to engage in higher and more risky alcohol use than their non-athlete peers [18][19][20], and it was found that one of the most frequently described reasons for alcohol use among athletes was to alleviate the stress of college life [17]. Due to the previous findings suggesting freshmen athletes experience unique stressors [13], this study will assess the impact of academic class on depression symptom severity.…”
Section: Daily Stressmentioning
confidence: 89%
“…Because there is no pre-selection for this conscription, a virtual census of the Swiss male population of this age can be obtained at the army recruitment facilities. Between August 2010 and November 2011, 13,245 young men present at three army recruitment centers were asked to participate in the study; 7,563 of them gave their informed written consent. The army environment was used for enrolment purposes only.…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13][14] A couple of longitudinal studies have also shown that drinking motives predict changes in alcohol use over time, e.g., higher enhancement motives predict an increase in RSOD 15,16 and higher enhancement or coping motives predict an increase in alcohol-related problems. [17][18][19] The theoretical model of drinking motives assumes that they also depend on reinforcement achieved through feedback loops from past drinking, 8,9,20 i.e., the experience of positive effects of drinking in a group is likely to encourage further drinking for social motives.…”
Section: Introductionmentioning
confidence: 99%
“…Intercollegiate athletes reported greater alcohol consumption, engaged in more frequent heavy episodic drinking, and reported more alcohol-related problems than their non-athlete peers (Grossbard et al, 2009;Hummer, LaBrie, & Lac, 2009;Martens, Dams-O'Connor, & Beck, 2006;Martens, Labrie, Hummer, & Pedersen, 2008;Weaver et al, 2013;Yusko, Buckman, White, & Pandina, 2008). Moreover, relative to non-athletes, athletes reported, not only greater alcohol use, but also more sexual partners and lower perceived risk as a cognitive mediator of unhealthy behavior (Wetherill & Fromme, 2007).…”
mentioning
confidence: 99%